The Urgency of Developing Student’s Interests and Talents in Educational Institutions - Aliffany Pualam Ariarta; Sumbulah, Umi; Aziz, Abdul (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to examine the importance of developing students' interests and talents, the stages that are passed in the process, and who plays a role in the process of developing students' interests and talents. This research uses a qualitative method with the type of literature study. Data collection is obtained from written sources, in the form of reading books, journals, scientific research and other documents relevant to the topic of discussion. Data analysis techniques with stages: 1) Condensation of data, 2) Presentation of data, 3) Describing data and verification of conclusions. The results showed that the development of interests and talents has an important urgency for students to help students discover and increase their potential, form self-identity and build self-confidence. It can also reduce cases of gadget addiction and online games for teenagers caused by a lack of positive activities. The establishment of interest and talent development activities needs to go through initial planning, implementation according to established standards, as well as regular control and evaluation so that it can be carried out properly. The role of teachers and parents is important for the success of this development activity. They help students find out their interests and talents, guide, become facilitators, motivators, and become role models.